History of alternative preventive therapies for type 1 diabetes mellitus - T. S. Khobotkova; N. N. Minyailova; O. V. Budnikova; A. V. Vedernikova (Кубанский научный медицинский вестник)
Background. Type 1 diabetes mellitus refers to one of the most prevalent chronic diseases. In recent years, a steady growth in this nosology has been registered in the Russian Federation, as well as globally, particularly among children and adolescents. Consequently, the number of children and adolescents classified as disabled by type 1 diabetes mellitus is also rising, prompting the global medical community to focus on mitigating these issues. The primary treatment for type 1 diabetes mellitus involves insulin replacement therapy combined with self-monitoring of blood glucose levels. Currently, insulin pumps and devices for continuous glucose monitoring have been developed and implemented in clinical practice, enhancing the effectiveness of type 1 diabetes mellitus treatment and significantly improving the quality and expectation of lives. However, even hybrid closed-loop systems (a combination of continuous subcutaneous insulin infusion and continuous glucose monitoring) fail to achieve physiological regulation of blood glucose levels and to completely eliminate the risk of long-term complications.Objectives. To explore the history of alternative preventive therapeutic methods for type 1 diabetes mellitus based on data from both Russian and international research literature.Methods. A comparative analysis of literature from both Russian and international authors addressing the issues of therapy and prevention of type 1 diabetes mellitus was conducted using the scientometric database eLibrary. ru and the biomedical search engine PubMed.Results. The search for alternative therapeutic methods that can prevent or delay the onset of the diabetes remains relevant. These therapeutic methods can be conditionally divided into conservative and surgical approaches,  primarily aimed at protecting pancreatic β-cells from immune-mediated destruction. Notable immunotherapeutic agents include antiproliferative agents, systemic immunomodulators, T-cell inhibitors, monoclonal antibodies, autoantigens, various types of stem cells, dendritic cells, and microbiota therapy.Conclusion. The paper presents several experimental methods of preventive therapy for type 1 diabetes mellitus and the results of studies conducted in this area, describes the proposed mechanisms for establishing immunological tolerance. A brief overview of completed and ongoing clinical trials is provided.